How universal are reserve design rules? A test using butterflies and their life history traits. Issue 5 (14th July 2015) - Bartonova, Alena; Benes, Jiri; Fric, Zdenek Faltynek; Chobot, Karel; Konvicka, Martin
Abstract : We used butterfly species lists available for a set of 125 Czech Republic National Nature Reserves and Monuments, the highest small‐sized conservation category in the country encompassing practically all biotope types existing in central Europe, to test the validity of generally agreed "reserve design rules" using multivariate ordination analyses. Further, we used ordination analysis of butterfly life history traits to seek for biological mechanisms responsible for butterfly community responses to essentially geometric reserves characteristics. Reserve area, relative perimeter, within reserve habitat heterogeneity, and surrounding landscape compositional and configurational heterogeneity all affected the composition of butterfly assemblages after controlling for effects of geographical position and prevailing biotope type. Species inclining towards large reserves displayed low mobility and high local population density, probably because they require large habitat areas to maintain self‐sustaining populations; such species tend to have restricted distribution in the country and threatened status. Reserves with relatively long boundaries hosted species with high mobility, broad trophic range and long adult period; faunas of such reserves contain high proportions of widespread generalists. Species with narrow trophic ranges inclined towards reserves containing diverse habitats, probably due to requirements for high floristic diversity. Species with short adult flight, low generations number and overwintering in early stages inclined towards reserves situated amidst diverse landscapes, perhaps because such species require finely‐grained mosaics for metapopulation dynamics. Commonly agreed reserve design rules thus hold for Central European butterflies, but different design characteristics are important for individual species, depending on their life histories.